At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To find the product of the functions [tex]\( f(x) = x + 3 \)[/tex] and [tex]\( g(x) = x - 3 \)[/tex], we need to multiply these two functions together.
Let's define the product of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] as [tex]\( h(x) \)[/tex].
So, [tex]\( h(x) = f(x) \cdot g(x) \)[/tex].
Substitute the expressions for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ h(x) = (x + 3) \cdot (x - 3) \][/tex]
Using the difference of squares formula [tex]\( (a + b)(a - b) = a^2 - b^2 \)[/tex]:
[tex]\[ h(x) = x^2 - 3^2 \][/tex]
Simplify the expression:
[tex]\[ h(x) = x^2 - 9 \][/tex]
Now let's evaluate [tex]\( h(x) \)[/tex] at a specific value of [tex]\( x \)[/tex]. For instance, let’s choose [tex]\( x = 1 \)[/tex]:
[tex]\[ h(1) = 1^2 - 9 \][/tex]
Calculate the value:
[tex]\[ h(1) = 1 - 9 \][/tex]
[tex]\[ h(1) = -8 \][/tex]
Thus, the product of the functions [tex]\( f(x) = x + 3 \)[/tex] and [tex]\( g(x) = x - 3 \)[/tex] evaluated at [tex]\( x = 1 \)[/tex] is:
[tex]\[ h(1) = -8 \][/tex]
Let's define the product of [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex] as [tex]\( h(x) \)[/tex].
So, [tex]\( h(x) = f(x) \cdot g(x) \)[/tex].
Substitute the expressions for [tex]\( f(x) \)[/tex] and [tex]\( g(x) \)[/tex]:
[tex]\[ h(x) = (x + 3) \cdot (x - 3) \][/tex]
Using the difference of squares formula [tex]\( (a + b)(a - b) = a^2 - b^2 \)[/tex]:
[tex]\[ h(x) = x^2 - 3^2 \][/tex]
Simplify the expression:
[tex]\[ h(x) = x^2 - 9 \][/tex]
Now let's evaluate [tex]\( h(x) \)[/tex] at a specific value of [tex]\( x \)[/tex]. For instance, let’s choose [tex]\( x = 1 \)[/tex]:
[tex]\[ h(1) = 1^2 - 9 \][/tex]
Calculate the value:
[tex]\[ h(1) = 1 - 9 \][/tex]
[tex]\[ h(1) = -8 \][/tex]
Thus, the product of the functions [tex]\( f(x) = x + 3 \)[/tex] and [tex]\( g(x) = x - 3 \)[/tex] evaluated at [tex]\( x = 1 \)[/tex] is:
[tex]\[ h(1) = -8 \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.